Determinants of Neural Tube Defects among Newborns in Amhara Region, Ethiopia: A Case-Control Study - Abay Woday Tadesse; Ayesheshim Muluneh Kassa; Setognal Birara Aychiluhm (International Journal of Pediatrics)
Background. Worldwide, an estimated 300,000 neonates are born with neural tube defects (NTDs) each year. However, NTDs are underreported in Ethiopia though it causes substantial mortality, morbidity, disability, and psychological and economic cost in the country. Moreover, the factors attributed to NTDs were not addressed. Hence, this study intended to identify the determinants of neural tube defects in Amhara Region, Ethiopia. Methods. A case-control study design was conducted among 400 newborns (133 cases and 267 controls) who were born at randomly selected public hospitals. Cases were identified using the physician diagnosis of confirmed NTDs, and the two consecutive controls were selected using a simple random sampling technique. The data analysis was done using Stata 14.0. Variables with p value < 0.25 in the bivariate analysis were entered into the multivariable logistic regression model, and a corresponding 95% confidence interval was used to identify the predictors of NTDs. Results. In this study, fifty percent (48%) of the cases were contributed by anencephaly. After controlling the covariates, living in rural areas (AOR=1.78: 95% CI 1.02, 3.11), being illiterate (AOR=1.81: 95% CI 1.07, 4.61), being female newborn (AOR=1.95: 95% CI 1.09, 3.50), having no ANC follow-up (AOR=1.93: 95% CI 1.17, 5.04), and having a previous history of NTDs (AOR=4.39: 95% CI 2.42, 7.96) were the risk factors for NTDs. However, being supplemented with folic acid or multivitamins before or during pregnancy (AOR=0.37: 95% CI 0.21, 0.65), never having taken any substance during pregnancy (AOR=0.42: 95% CI 0.21, 0.88), and being free from medical illnesses during pregnancy (AOR=0.27: 95% CI 0.11, 0.69) were the protective factors of NTDs. Conclusion. The study revealed different factors associated with NTDs among newborns in the region. Therefore, comprehensive preventive strategies focused on identified risk factors are needed at regional and national levels.